2008
DOI: 10.1073/pnas.0807643105
|View full text |Cite
|
Sign up to set email alerts
|

Ancient origin of the gene encoding involucrin, a precursor of the cross-linked envelope of epidermis and related epithelia

Abstract: The cross-linked (cornified) envelope is a characteristic product of terminal differentiation in the keratinocyte of the epidermis and related epithelia. This envelope contains many proteins of which involucrin was the first to be discovered and shown to become cross-linked by a cellular transglutaminase. Involucrin has evolved greatly in placental mammals, but retains the glutamine repeats that make it a good substrate for the transglutaminase. Until recently, it has been impossible to detect involucrin outsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 37 publications
1
49
0
Order By: Relevance
“…The Sprr multigene family is instrumental in the formation of a cornified envelope (CE), which serves as a protective barrier in various stratified squamous epithelia (27). Moreover, we observed that genes encoding CE structural proteins, including involucrin, cornifelin, and cytokeratin 4, were also upregulated in KO cTEC (28,29). Taken together, these results suggest that Aire 2/2 cTEC acquire a more differentiated phenotype by upregulation of genes involved in CE formation.…”
Section: Aire Has Non-cell Autonomous Effects On the Ctec Transcriptomesupporting
confidence: 66%
“…The Sprr multigene family is instrumental in the formation of a cornified envelope (CE), which serves as a protective barrier in various stratified squamous epithelia (27). Moreover, we observed that genes encoding CE structural proteins, including involucrin, cornifelin, and cytokeratin 4, were also upregulated in KO cTEC (28,29). Taken together, these results suggest that Aire 2/2 cTEC acquire a more differentiated phenotype by upregulation of genes involved in CE formation.…”
Section: Aire Has Non-cell Autonomous Effects On the Ctec Transcriptomesupporting
confidence: 66%
“…The localization of betaprotein genes in the EDC of both Gallus gallus and Anolis carolinensis has been found between the loricrin gene and the involucrin-trichohyalin-like genes, and this suggests that the genes for beta-proteins derived from a modification of ancestral genes common for a precursor EDC-protein, indicated as simple EDC proteins (SEDC, Strasser et al 2014). Therefore, in sauropsid genomes, the genes coding for corneous betaproteins evolved in regions that in mammalian genomes are instead occupied by mammalian-specific genes coding for other EDC-corneous proteins (Vanhoutteghem et al 2008;Strasser et al 2014). Comparative genomics therefore further confirms that proteins formerly termed beta-keratins Fig.…”
Section: And 1 S D)mentioning
confidence: 96%
“…The latter enable different skin derivatives such scales, claws, beaks, horns, and feathers to perform their specific functions. Recent genomic studies have also shown that genes for "beta-keratins" in both the chick and lizard are clustered within the "epidermal differentiation complex" locus (EDC), together with the genes for other corneous proteins, and are not linked to alpha-keratins loci (Vanhoutteghem et al 2008;Eckhart et al 2008;Mlitz et al 2014;Strasser et al 2014;Figs. 3 …”
Section: Beta-keratins Are Sauropsid Corneous Beta-proteinsmentioning
confidence: 98%
See 1 more Smart Citation
“…The other antibodies were kindly provided by Pr Danielle Dhouailly for αK-11E10 (keratin 14) (Collomb et al, 2013), by Dr Furuse for anti-occludin (Furuse et al, 1993) and by Dr Philippe Djian for anti-involucrin (Vanhoutteghem et al, 2008).…”
Section: Antibodiesmentioning
confidence: 99%